Fungsi Lensa Berwarna Pada Myopia Tinggi Untuk Mengurangi Aberasi - Wahyu Budiana; Zakaria Efendi; Opep Cahya Nugraha (Akademi Refraksi Optisi dan Optometry Gapopin, 2022)
Complaints of high myopia sufferers who use minus glasses generally are excessive glare and visual discomfort when used to see detailed objects, this can be caused by aberrations in the lens. This study aims to determine the function of colored lenses in reducing the occurrence of aberrations in myopia sufferers. This research uses descriptive analysis method. The results showed that the use of colored lenses in high myopia patients who wear minus glasses can reduce glare and provide comfort in detailed vision.